Kepatuhan Syariah dalam Pengelolaan Haji dan Umrah: Tinjauan Kualitatif terhadap Kebijakan dan Implementasinya di Indonesia - Mahera, Rofiqo Meili; S, Syahpawi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The country with the largest Muslim population in the world, the management of pilgrimage and Umrah is not only an administrative responsibility, but also a religious trust that must comply with the principles of sharia economics. This research aims to analyze the level of Shariah compliance in the management of Hajj and Umrah in Indonesia through a study on its policies and implementation. The research method adopted was a descriptive qualitative approach with data collection techniques in the form of in-depth interviews with policy makers in the Ministry of Religious Affairs, Hajj Financial Management Agency (HJM) managers, as well as Umrah industry actors. Additionally, a documentation study of formal regulation as well as observation of practices in the field was conducted. The study results show that from a regulatory aspect, the Indonesian government has built a legal and institutional framework that supports the implementation of Hajj and Umrah based on Shariah principles. However, in its implementation there are still a number of challenges, such as lack of transparency of fund management, uneven service quality of Umrah pilgrimage trip organizers (PPIU), as well as weak Shariah supervision at the operational level. Some PPIUs have not fully implemented the principles of accountability and trustworthiness in service to the congregation. On the other hand, the management of funds by BPKH has led to Shariah investment, but still needs refinement to be more convenient and oriented to the interests of the congregation. The study recommended the strengthening of Shariah-based supervision systems, improved Shariah literacy for practitioners and congregants, as well as optimizing the Shariah Supervisory Board’s role in overseeing every stage of Hajj and Umrah management. Thus, Shariah compliance in the management of pilgrimage and Umrah in Indonesia can be realized thoroughly and sustainably